2017
DOI: 10.1093/mnras/stx302
|View full text |Cite
|
Sign up to set email alerts
|

Dust traps as planetary birthsites: basics and vortex formation

Abstract: We present a simple model for low-mass planet formation and subsequent evolution within "transition" discs. We demonstrate quantitatively that the predicted and observed structure of such discs are prime birthsites of planets. Planet formation is likely to proceed through pebble accretion, should a planetary embryo (M 10 −4 M ⊕ ) form. Efficient pebble accretion is likely to be unavoidable in transition disc dust traps, as the size of the dust particles required for pebble accretion are those which are most ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 99 publications
0
24
1
Order By: Relevance
“…Regarding the baroclinic perturbations, although they are known to produce vortical instabilities in protoplanetary disks (Klahr & Bodenheimer 2003;Petersen et al 2007a,b;Lesur & Papaloizou 2010;Raettig et al 2013;Barge et al 2016), they have been rarely considered in relation to hot protoplanets. For example, Owen & Kollmeier (2017) claim that that hot protoplanets can excite large-scale baroclinic vortices but we do not identify any of those in our simulations. Instead, we find baroclinic perturbations to be responsible for 3D distortion of the gas flow near the protoplanet.…”
Section: Relation To Previous Workcontrasting
confidence: 60%
“…Regarding the baroclinic perturbations, although they are known to produce vortical instabilities in protoplanetary disks (Klahr & Bodenheimer 2003;Petersen et al 2007a,b;Lesur & Papaloizou 2010;Raettig et al 2013;Barge et al 2016), they have been rarely considered in relation to hot protoplanets. For example, Owen & Kollmeier (2017) claim that that hot protoplanets can excite large-scale baroclinic vortices but we do not identify any of those in our simulations. Instead, we find baroclinic perturbations to be responsible for 3D distortion of the gas flow near the protoplanet.…”
Section: Relation To Previous Workcontrasting
confidence: 60%
“…In this work, we have found that high dust-to-gas ratio clumps form in the inner regions of discs around unequal-mass, eccentric, and inclined binaries (especially for polar configurations). Such clumps could then constitute sweet spots for dust accumulation and grain growth (Gonzalez et al 2017;Owen & Kollmeier 2017), suggesting that CBDs could potentially be efficient planetesimal cradles.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, finding a concentrated asymmetry would not necessarily indicate a planet formed rapidly. It might instead suggest that the vortex did not form until after the planet finished growing, that other factors such as thermodynamic effects shaped the asymmetry (Owen & Kollmeier 2017), or that a planet may not be responsible for the feature in the disc.…”
Section: Comparisons To Theoretical Modelsmentioning
confidence: 99%